2021
DOI: 10.1101/2021.02.28.433291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural O-Glycoform Heterogeneity of the SARS-CoV-2 Spike Protein Receptor-Binding Domain Revealed by Native Top-Down Mass Spectrometry

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) utilizes an extensively glycosylated surface spike (S) protein to mediate host cell entry and the S protein glycosylation is strongly implicated in altering viral binding/function and infectivity. However, the structures and relative abundance of the new O-glycans found on the S protein regional-binding domain (S-RBD) remain cryptic because of the challenges in intact glycoform analysis. Here, we report the complete structural characterization of int… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
2
5
0
Order By: Relevance
“…[28][29][30][31][32] Two recent publications have used top-down mass spectrometry to study RBD glycosylation. 33,34 Both of these studies identified O-glycosylation at site T323 of the spike S1 protein and two Nglycosylation sites at N331 and N343, the same sites that were previously identified with bottom-up glycoproteomics. 3,19,20 The study from Roberts et al, 34 used denatured and native top-down analysis to determine the relative abundance of O-glycoforms of the RBD, while the study from Gstöttner et al 33 combined bottom-up, and intact protein analysis with multiple glycosidase enzymatic steps to study the N-and O-linked glycosylation profile of the RBD.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…[28][29][30][31][32] Two recent publications have used top-down mass spectrometry to study RBD glycosylation. 33,34 Both of these studies identified O-glycosylation at site T323 of the spike S1 protein and two Nglycosylation sites at N331 and N343, the same sites that were previously identified with bottom-up glycoproteomics. 3,19,20 The study from Roberts et al, 34 used denatured and native top-down analysis to determine the relative abundance of O-glycoforms of the RBD, while the study from Gstöttner et al 33 combined bottom-up, and intact protein analysis with multiple glycosidase enzymatic steps to study the N-and O-linked glycosylation profile of the RBD.…”
Section: Introductionsupporting
confidence: 62%
“…28,39 Variable amounts of sialic acid groups on the O-and the N-glycan sites have been reported on the RBD. 20,33,34 Separation techniques to resolve these complex RBD glycoforms have not been systematically evaluated to the best of our knowledge. One might expect CZE to separate the RBDs well since there is some variance in charged sialic acid, while HILIC may be able to separate the more neutral N-glycans based on total glycan composition.…”
Section: Results and Discussion: Hilic Provided The Highest Degree Of Separation For Resolving The Heterogeneity Of Rbd Glycoforms By Sepmentioning
confidence: 99%
See 3 more Smart Citations